(untitled) (Revista Brasileira Multidisciplinar, 2022)
Abstract When human physiological needs are affected, some therapies to be achieved may require specific resources, such as the use of biomaterials. Thus, to support life, various devices have been developed over the years, such as probes/catheters for the digestive, respiratory, urinary, and vascular systems, among others. These medical devices differ from the constitution of the materials to the designs. In this universe, we chose to discuss venous catheters in terms of dimensions, durability, insertion, infection/biofilm, material, innovations, technological advances and adverse events. The study was carried out through a systematic literature review on pubmed, academic google and complementary materials were listed because they could make it possible to raise these criteria and contribute with fundamental information to the understanding of the interaction of the catheter with the blood. The relevance of the present study is due to the interdisciplinary overview focused on the venous catheter. It was noticed that the technological development of these medical devices took place over the years, however, conflicting traits about the catheter are still found in the literature, it is mentioned: the obstruction by blood clot related to the use of anticoagulant x saline solution as forms of solve the problem; different recommendations on the durability of the catheter linked to the material type. Therefore, it was concluded that the circumstances of the venous catheter are complex, as are the substrate/blood interface relationships and adverse events. It is noted that the events associated with the catheter have an interdisciplinary character, involving knowledge of biotechnology, pharmacology, nursing, engineering, etc.